KORELASI VARIABILITAS DISTRIBUSI BINTIK MATAHARI TERHADAP ANOMALI TEMPERATUR PERMUKAAN BUMI DI KAWASAN ASIA TENGGARA TAHUN 1874-2019 - Khoiroh, Kurnia
The sun is the center of the solar system as the main source of energy for the Earth. One of the activities of the sun is sunspots, which are dark areas on the sun's surface that are influenced by magnetic activity in the photosphere layer of the sun. The movement of the Earth around the Sun and rotating on its axis affects the amount of energy emitted by the Sun so that there are large differences in the radiation received by each place on Earth and results in differences and changes in the climate of each place. Southeast Asia, which is located around the Earth's equator, gets the most solar radiation. Climate change can be influenced by solar activity. The Final Project Discussion uses daily Sunspots catalog data from 1874 to 2019 and monthly temperature anomalies of the Earth's surface in the same time range for Indonesia, Singapore, Malaysia, Thailand, Philippines, Laos, Vietnam, Myanmar, and Cambodia. The analysis of the variability of the sunspot distribution will utilize the statistics of the long sunspot data, namely north-south asymmetry, sunspot cycle parameters, and the position of the active latitude range. Sunspot correlation and north-south asymmetry number of sunspots and area of sunspots with the Earth's surface temperature anomaly using the sunspot catalog data and the annual Earth's surface temperature anomaly that have been processed previously. The results show that there are plots of distribution results for the parameters of sunspot latitude, Photometric Sunspot Index (PSI), projected sunspot area, and corrected sunspot area which show temporal variations of sunspot cycles. The correlation Photometric Sunspot Index (PSI) and the area of sunspots corrected with the Earth's surface temperature anomaly in 1874 - 2019 is very small. Likewise, the correlation between the asymmetry of the number of sunspots and the asymmetry of the area of the sunspots in 1874 – 2019 is corrected for a small value. However, if we look at the years 1874 – 1970 and 1971 – 2019 for the correlation of the asymmetry of the number of sunspots and the asymmetry of the area of the sunspots that are corrected, the correlation value is greater than for the whole data.